The Influence of Monitoring, Evaluation, Supervision and Teamwork Effectiveness on the Implementation of the 7 Principles Correct of Drug Administration in Non-Covid-19 Inpatient Installations in Hospitals - Pratama Zendrato; Rafael Ginting; Santy Deasy Siregar (International Journal of Health and Pharmaceutical (IJHP), 2023)
The purpose of this study was to analyze the influence of monitoring, evaluation, supervision and teamwork effectiveness on the implementation of the seven Correct principles of drug administration at the Hospital in Pematang Siantar and compare the theory. The author studied by collecting data using various literature studies, questionnaires which were arranged as instruments to obtain quantitative data with a Likert scale system which were distributed to 103 respondents. This research is quantitative analytic with cross sectional approach. The research was conducted at Hospital in Pematang Siantar. The research population was 103 people and all of them were used as samples (total sampling). Data analysis was univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at 95% confidence level (α=0.05). The results showed that the implementation of the 7 principle was correct in administering drugs in the non-Covid-19 Inpatient Installation of Hospital Pematang Siantar was influenced by monitoring variables (p=0.000), evaluation (p=0.036), teamwork effectiveness (p=0.042). While the variable that has no effect is supervision (p = 0.405). The monitoring variable has a greater influence on the implementation of the 7 principles correctly administering drugs with a value of OR = 10,643 meaning that nurses who state that monitoring is good have the opportunity to implement the 7 principals correct of giving drugs properly by 10.6 times higher than nurses who state that monitoring is not good. The conclusion of the study is that monitoring, evaluation and effectiveness of teamwork affect the implementation of the 7 principles correct of drug administration. It is recommended that the hospital can carry out continuous monitoring and evaluation related to the procedures that have been set as a benchmark for achieving SOPs that are applied in implementing the 7 principles correct of drug administration. Nurses need to improve the effectiveness of teamwork (teamwork) so as to minimize the adverse impact on the patients served.